Neuropeptides and the Nodes of Ranvier in Cranial Headaches - Edvinsson, Jacob C. A.; Haanes, Kristian A.; Edvinsson, Lars (Frontiers in Physiology, 2022)
The trigeminovascular system (TGV) comprise of the trigeminal ganglion with neurons and satelitte glial cells, with sensory unmyelinated C-fibres and myelinated Aδ-fibres picking up information from different parts of the head and sending signals to the brainstem and the central nervous system. In this review we discuss aspects of signalling at the distal parts of the sensory fibres, the extrasynaptic signalling between C-fibres and Aδ-fibres, and the contact between the trigeminal fibres at the nerve root entry zone where they transit into the CNS. We also adress the possible role of the neuropeptides calcitonin gene-related peptide, the neurokinin family and pituitary adenylyl cyclase-activating polypeptide 38, all found in the TGV system together with their respective receptors. Elucidation of the expression and localization of neuropeptides and their receptors in the TGV system may provide novel ways to understand their roles in migraine pathophysiology and suggest novel ways for treatment of migraine patients.